1999
DOI: 10.1002/(sici)1098-0997(1999)7:3<158::aid-idog8>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

A matched prospective study of human immunodeficiency virus serostatus, human papillomavirus DNA, and cervical lesions detected by cytology and colposcopy

Abstract: Objective: To compare the prevalence and type of human papillomavirus (HPV) infections in the genital tract of human-immunodeficiency-virus- (HIV) seropositive and -seronegative women matched for cytology and to examine prospectively the relationship of HPV DNA, colposcopic findings and cervical squamous intraepithelial lesions (SIL) in these matched seropositive and seronegative cohorts.Methods: A matched prospective study of HIV-seropositive and -seronegative women undergoing cytologic screening, colposcop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…TSCOT represents a possible risk factor in 9q32 and the encoded protein might inXuence the ability of T-lymphocytes to recognize and eradicate HPV infections. HPV persistence has been associated with malignant cervical epithelial neoplasia (Ho et al 1995;Schlecht et al 2001) and in order to establish long term infection, HPV needs to escape recognition and eradication by T-cells (Critchlow et al 1998;Eckert et al 1999;Hillemanns et al 1996;MinkoV et al 1998;Palefsky et al 1997;Palefsky et al 1998;Sun et al 1997). Women with low MAAD may have been inXuenced by tumour suppressor genes and oncogenes that together with HPV infection caused a faster progression and an earlier onset of disease.…”
Section: Discussionmentioning
confidence: 99%
“…TSCOT represents a possible risk factor in 9q32 and the encoded protein might inXuence the ability of T-lymphocytes to recognize and eradicate HPV infections. HPV persistence has been associated with malignant cervical epithelial neoplasia (Ho et al 1995;Schlecht et al 2001) and in order to establish long term infection, HPV needs to escape recognition and eradication by T-cells (Critchlow et al 1998;Eckert et al 1999;Hillemanns et al 1996;MinkoV et al 1998;Palefsky et al 1997;Palefsky et al 1998;Sun et al 1997). Women with low MAAD may have been inXuenced by tumour suppressor genes and oncogenes that together with HPV infection caused a faster progression and an earlier onset of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Such individuals show increased prevalence of anogenital HPV infection (31,32,60,(105)(106)(107) as well as longer periods of HPV persistence (31,40,46,90,136). In addition, infection with multiple HPV types and with oncogenic types are more common (9,31,46,78,90,107,136). Associations between markers of HIV disease status (e.g., viral load and CD4 lymphocyte count) and HPV infection have been inconsistent.…”
Section: School Of Medicine University Of California San Francisco mentioning
confidence: 99%
“…Such individuals show increased prevalence of anogenital HPV infection (31, 32, 60, 105-107) as well as longer periods of HPV persistence (31,40,46,90,136). In addition, infection with multiple HPV types and with oncogenic types are more common (9,31,46,78,90,107,136).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22 In the 1990s, as the diagnosis of HPV infection by molecular diagnosis was developed, there were many reports confirming the rise in the incidence of infection with HPV 23 and other comorbidities, which included warts 24 and cervical squamous intraepithelial lesions 25 in patients who were immunosuppressed. The association of reduced cell-mediated immunity and consequent increase in HPV infection and associated disease in HIV-infected individuals has been demonstrated in various studies wherein these patients have shown increased prevalence [26][27][28][29][30][31] and longer period of persistence of HPV infection, 26,[32][33][34][35] which also provides a strong evidence to support the role of cell-mediated immunity. One of the major limitations in studies of cellmediated immune responses to HPV infection due to its highly localized nature of tissue tropism is squamous epithelial sites.…”
Section: Discussionmentioning
confidence: 99%